Detection of chloramphenicol residue in bovine meat using Liquid Chromatography Mass Spectrometry - R, Widiastuti; Y, Anastasia (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Chloramphenicol (CAP) is a broad spectrum antibiotic that has been banned in many countries due to its serius side effect to human. Detection of CAP residue in food has been determined to a minimum required performance limit (MRPL) of 0.3 ng/g. The purpose of this research was to conduct the analysis of CAP residue in bovine meat by using LCMS and to study the presence of CAP residue in marketed bovine meat samples. LC separation was done on a Shimpack column C18 with ammonium acetate 10 mM/water as mobile phase, and ESI-MS analysis in negative ion mode. The coefficient of determination, R2 = 0.9981 at concentration of 0.125, 0.25, 0.63, 1,00 and 2.00 ng/g. Recovery at three fortification levels (0.25, 0.50 and 1.00 ng/g) was in the range 77.5, 97.3 and 83.4%. The decision limit and the detection capability were 0.15 ng/g and 0.17 ng/g respectively. Analysis results of 52 marketed samples showed that CAP residue were detected in 9 samples in the concentration range of 0.14 to 2.70 ng/g and 6 among those positive samples were above the MRPL value. Therefore, it is important to increase the awareness and also to monitor regularly CAP residues in food originated from animal to provide safe food for the consumers. Key Words: Chloramphenicol, Residue, LCMS, Bovine Meat